THE EFFECTIVENESS OF COGNITIVE BEHAVIORAL GROUP THERAPY PROGRAM IN ENHANCING PSYCHOLOGICAL RESILIENCE OF PARENTS OF CHILDREN WITH CANCER IN JERUSALEM - Elyan, Hassan (An-Najah National University, 2025)
Abstract Background: The researcher identified a gap in the availability of psychological support specifically tailored to enhance the resilience of parents of children with cancer in Jerusalem. Observing these parents' struggles and recognizing the potential for cognitive behavioral therapy (CBT) to foster resilience, the researcher felt compelled to address this unmet need. Objectives of the study: this study investigates the effectiveness of a structured CBT program in enhancing the psychological resilience of parents of children with cancer in Jerusalem. Method: The study population consists of parents of Palestinian children with cancer, whose children are receiving treatment at hospitals in Jerusalem such as Al‑Mutlaa Hospital, Al‑Maqasid Hospital, and Hadassah Ein Kerem Hospital, a total of 18 participants were randomly and equally assigned to two groups, the experimental group and the control group, each consisting of nine parents, the experimental group comprises six women (66.7 %) and three men (33.3 %), in terms of age a slight majority of the parents are over 35 years old (five participants, 55.6 %) while four participants (44.4 %) are younger than 36 years old. Findings : The results revealed a moderate level of psychological resilience among the parents of children with cancer, indicating that they generally maintain a reasonable capacity to cope with psychological challenges, the findings also show that the cognitive-behavioral group therapy program was highly effective in enhancing psychological resilience among these parents, this conclusion is supported by the significant improvements observed in various domains of psychological resilience from the pre-test to the post-test, the experimental group, which participated in the program, demonstrated marked progress in self-confidence, adjustment to changes and stress, perseverance and persistence, coping with problems and stress, and seeking supportive resources. Keywords: CBGTP (Cognitive Behavioral Group Therapy Program), Psychological Resilience, Parents, care in Jerusalem.
فعالية برنامج العلاج السلوكي المعرفي الجمعي في تحسين المرونة النفسية لأولياء أمور الأطفال المصابين بالسرطان في القدس